Canopy soil greenhouse gas dynamics in response to indirect fertilization across an elevation gradient of tropical montane forests. (29th November 2016) - Matson, Amanda L.; Corre, Marife D.; Veldkamp, Edzo
Abstract: Canopy soils can significantly contribute to aboveground labile biomass, especially in tropical montane forests. Whether they also contribute to the exchange of greenhouse gases is unknown. To examine the importance of canopy soils to tropical forest‐soil greenhouse gas exchange, we quantified gas fluxes from canopy soil cores along an elevation gradient with 4 yr of nutrient addition to the forest floor. Canopy soil contributed 5–12 percent of combined (canopy + forest floor) soil CO2 emissions but CH4 and N2 O fluxes were low. At 2000 m, phosphorus decreased CO2 emissions (>40%) and nitrogen slightly increased CH4 uptake and N2 O emissions. Our results show that canopy soils may contribute significantly to combined soil greenhouse gas fluxes in montane regions with high accumulations of canopy soil. We also show that changes in fluxes could occur with chronic nutrient deposition.